Conectividade e panorama da produção científica: o caso da Psicologia Política brasileira - Veiga, Maria Aparecida Cunha Malagrino (2022)
Mapping the scientific production of researchers in the field of Political Psychology was the aim of this study. For this, it was necessary to identify academic training, institutional affiliation, title, bibliographic production, guidance and participation in master's and doctoral committees, in addition to collaboration in the organization and participation in scientific and cultural events. It is understood that verifying the scientific production corroborates to measure the quantity of this production, but also to reveal the collective efforts, the centrality, the density, to point out leaderships and the nodal points. Thus, this research mapped 52 researchers over a period of 22 years. Such characters participated in management positions and on the Fiscal Council of the board of the Brazilian Association of Political Psychology (ABPP) constituted in December 2000. A descriptive study with a mixed approach was carried out. Initially, a set of documents was used to know the state of the art, then a centimetric research was carried out in the database of the Lattes Platform, Acacia Platform, Capes Catalog of Theses and Dissertations and open access digital platforms. The analysis of the data obtained from the scientific production will be submitted to Social Network Analysis (ARS) techniques and the universe of Academic Genealogy connections. Such results are presented through charts, figures, tables and texts. It is concluded that between 2000 and 2022, 78 books, 970 book chapters and 1512 articles, 780 master's and doctoral supervisions, 44 post-doctoral supervisions were published. The production found represents the efforts of researchers to strengthen the field of Political Psychology, and the recognized density has the potential to encourage and boost new researchers and new paths for the expansion and strengthening of the area